2023
DOI: 10.3390/healthcare11060801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Binaural Beats Stimulation of Gamma Frequency over Memory Performance and EEG Spectral Density

Abstract: Similar to short-term memory, working memory cannot hold information for a long period of time. Studies have shown that binaural beats (BB) can stimulate the brain through sound, affecting working memory function. Although the literature is not conclusive regarding the effects of BB stimulation (stim) on memory, some studies have shown that gamma-BB stim (40 Hz) can increase attentional focusing and improve visual working memory. To better understand the relationship between BB stim and memory, we collected el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…This holistic approach can lead to improvements in memory, response inhibition, and cognitive organization, contributing to anxiety reduction as evidenced in both post-test and follow-up phases of this study. The use of a 40 Hz BB, corresponding to gamma rhythm, in previous studies [ 58 , 59 , 60 , 61 ] has shown positive effects on stress reduction and cognitive function enhancement, consistent with the findings of this investigation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This holistic approach can lead to improvements in memory, response inhibition, and cognitive organization, contributing to anxiety reduction as evidenced in both post-test and follow-up phases of this study. The use of a 40 Hz BB, corresponding to gamma rhythm, in previous studies [ 58 , 59 , 60 , 61 ] has shown positive effects on stress reduction and cognitive function enhancement, consistent with the findings of this investigation.…”
Section: Discussionsupporting
confidence: 92%
“…The rhythmic influence on brain dynamics, particularly through activities like drumming, underscores the potential of BB in modulating consciousness states and frontal cortical activity [ 58 , 59 , 60 , 61 ]. The anxiolytic effects of BB, particularly at 40 Hz, may involve changes in frontal EEG synchrony, with implications for anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“… Jirakittayakorn and Wongsawat (2017) discovered no overall difference in word recall accuracy in participants who listened to 40-Hz binaural beats. Similarly, other studies have reported no short-term memory enhancement effects of 40-Hz stimulation ( Borges, Arantes, & Naves, 2023 ; Shekar et al., 2018 ). Ross and Lopez (2020) found that participants who listened to 40-Hz binaural beats on the first day and 16 Hz on the second day performed better in an attentional blink-related task compared with the group with the reverse order, but there were no differences on the third day.…”
Section: Introductionmentioning
confidence: 53%